The Dynamic Effect of Pile Installation in Sand on Nearby Piles - AlSheakayree, Talib K. Qassim; Shafiqu, Qassun S. Mohammed; Ibraheem, Asma T. (Al-Nahrain Journal for Engineering Sciences, 2017)
Driven piles have often been used in many civil structures to provide structural loading support. However, the unavoidable vibrations induced by pile driving processes may cause varying degrees of damage to adjacent structures. This research presents experimental studies to investigate the transmitted vibrations induced by impact of pile driving on vicinity piles. In the experimental work, a small scale model was tested in a sand box (steel container 1 × 1.5 × 0.8 m) with pile driving hammer device to install the impact pile in sand soil by dropping weights (1, 2, 3, 4 and 5 kg) for different heights of falling (4, 8, 12, 16 and 20 cm). The peak particle velocity was measured at a head of the vicinity piles by vibration meter device. In this study, several piles on different distances away from the vibration source were studied. The experimental results indicate that the peak particle velocity for vibrations emitted with impact pile driving is increased with increasing the energy and the penetration depth of pile driving for all vicinity piles and it can be decreased without change in the driving energy by decreasing the weight of hammer and increasing the height of falling hammer. Vibration intensities are attenuated with increasing surface distance from the pile driving and the peak particle velocity decreased uniformly with surface distance from the pile driving for piles. Also, through laboratory model representation and evaluation of the results obtained in the laboratory, the empirical relations which were determined based on the scaled-distance concept, are appropriate and give results very close and can be relied upon to represent the transmission of vibration resulting from the impact of pile driving to nearby piles.